38 Clinical features and echocardiographic parameters of relative adrenal insufficiency (RAI) among preterm infants: A five-year review. (29th October 2021) - Grewal, Gurpreet; Ting, Joseph; Lam, Carol; Yadav, Krishan; Kuan, Mimi
Abstract: Primary Subject area: Neonatal-Perinatal Medicine Background: Infants born at low gestational age (GA) often present with a septic shock-like picture in the neonatal intensive care unit (NICU). Some of these premature infants are noticed to exhibit inadequate cortisol levels at such a time of stress, an entity termed 'relative adrenal insufficiency' (RAI), which is postulated to compromise the compensatory mechanisms and further circulatory collapse. Objectives: To review the clinical features and echocardiographic parameters of RAI in preterm infants, and their correlation with adrenocorticotropic hormone (ACTH) stimulation tests in a quaternary NICU over 5 years. Design/Methods: This is a single centre retrospective study. Infants born at < 32 weeks GA between January 2015 to June 2019, admitted to the British Columbia Women's Hospital NICU (Vancouver, British Columbia), were reviewed. Infants who presented with a shock-like picture with a cortisol level at this time of stress of < 250 nmol/L were included. Infants who have received corticosteroid prior to cortisol collection were excluded. Results: There were 798 infants < 32 weeks admitted to the BCWH NICU over a 5 year period, of which 284 had a spot cortisol drawn. We identified 45 eligible infants in our study (5.6% of NICU admissions). Their median (IQR) for GA, birth weight, cortisol level, and age of onset of RAI were 25 weeks (24, 26), 690 g (590, 815), 83 (58, 127), and 13 days of life (8, 24), respectively. Among these infants, 73% developed significant hypotension or respiratory failure (Table 1). 13 infants (28.9%) had echocardiogram performed at the time of cardiopulmonary deterioration, and all had normal left ventricular (LV) fractioning shortening (median [IQR]: 42% [38-49%]) and LV output (median [IQR]: 242 mL/kg/min [155-330 mL/kg/min]). Only 19 infants (42.2%) received hydrocortisone, with a median [range] treatment duration of 2 days [1–8]. Lower cortisol level was associated with lower GA at the presentation of RAI (p=0.049), but not predictive of adverse clinical and laboratory outcomes (Table 2). ACTH stimulation tests were performed in 20 (44.5%) infants and 3 (15%) were found to be abnormal, and results were not correlated with clinical features. Conclusion: In our cohort, we identified 5% of NICU admission with RAI, based on the cut-off of cortisol < 250 nmol/L at the time of shock-like presentation. Lower cortisol level was associated with lower GA at the presentation of RAI. Further prospective study with a well-defined protocol is needed to understand the use of cortisol and its clinical implications.